2017
DOI: 10.1099/ijsem.0.001901
|View full text |Cite
|
Sign up to set email alerts
|

Paenibacillus polysaccharolyticus sp. nov., a xylanolytic and cellulolytic bacteria isolated from leaves of Bamboo Phyllostachys aureosulcata

Abstract: A novel xylanolytic and cellulolytic strain, BL9 T , was isolated from leaves of the Bamboo plants maintained at the Tamil Nadu Agricultural University Campus, Coimbatore, India. On the basis of the results of 16S rRNA gene analysis, it was determined to be phylogenetically close to the type strains of Paenibacillus amylolyticus NRRL NRS-290 T (98.3 %), Paenibacillus barcinonensis BP-23 T (98.1 %), Paenibacillus tundrae A10b T (98.0 %) and Paenibacillus xylanexedens B22a T (97.6 %). The strain stained Gram var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Despite not having found a core microbiota in the feathers, the most prevalent bacteria in waxbill feathers may be plant symbionts (e.g. Methylobacterium–Methylorubrum and Pantoea ; Dutkiewicz et al 2016, Madhaiyan et al 2017, Green and Ardley 2018) and are similar to variants found in another study in stones and soil (e.g. Sphingomonas ; Schröer et al 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Despite not having found a core microbiota in the feathers, the most prevalent bacteria in waxbill feathers may be plant symbionts (e.g. Methylobacterium–Methylorubrum and Pantoea ; Dutkiewicz et al 2016, Madhaiyan et al 2017, Green and Ardley 2018) and are similar to variants found in another study in stones and soil (e.g. Sphingomonas ; Schröer et al 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Pairwise average nucleotide identity comparison of this draft genome against all 217 public Paenibacillus genomes available through IMG revealed no other genome above the recommended species cutoff (ANI ≥ 96.5 and AF ≥ 0.6) [ 46 ]. The most closely related genome, Paenibacillus phyllostachyicola BL9 ( Paenibacillus polysaccharolyticus BL9T) [ 31 ], had an ANI of 93.2% with an AF of 0.84. The ANI of the next most related genome, Paenibacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Several stains of Paenibacillus , isolated from diverse sources such as soil, bamboo leaves, decomposing rice straw and decaying woods, harbour enzymes that are involved in cellulose and xylan degradation (Nelson et al ., 2009 ; Khianngam et al ., 2011 ; Ghio et al ., 2012 ; Madhaiyan et al ., 2017 ). Our genome analysis of S150 revealed no gene involved in lignin degradation but several ones linked to cellulose, and xylose and xylan (xyloside) degradation.…”
Section: Discussionmentioning
confidence: 99%